Spillover effects of work–family conflict on job consequences influencing work attitudes - Long Kim; Pattarawadee Maijan; Sook Fern Yeo (Scientific Reports)
Abstract A society risks experiencing inadequate educational services from higher education institutions if severe shortages of lecturers persist. Addressing such a critical social issue necessitates prioritizing lecturer satisfaction, as it is intrinsically linked to lecturer retention, reduced turnover rates, institutional cohesion, lecturer well-being, professional teaching development, and enhanced research and publication outcomes. The study aims to investigate the spillover effects of work–family conflict on job-related consequences, specifically stress and burnout, which subsequently shape work attitudes such as lecturer satisfaction, with occupational experience examined as a moderating variable. Data were collected from 450 Thai lecturers through a survey questionnaire, and a path analysis technique was employed for data analysis. The findings revealed that work–family conflict significantly influenced lecturer stress, which, in turn, was a key predictor of burnout. Additionally, burnout was found to significantly impact lecturer satisfaction, whereas stress did not directly influence satisfaction making burnout act as the mediator between stress and satisfaction. Furthermore, occupational experience moderated the relationship between burnout and lecturer satisfaction, highlighting its critical role in mitigating the adverse effects of burnout on overall work attitudes.